(3GdcTa hGdHjGf ef JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg CKfGA JaSjQ bhdg JYGdi (B" (3GdPjf cPHhG TYjHkG cCf de jZfhG ajgG (B" (3ef ShQI GdCYQGa s
(3BNQgG (B:s
(3jfJgi HJaSjQ BNQ ShQI GdJhHI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs